Supervision experiences of postgraduate research students at one South African higher education institution - Cekiso, M.; Tshotsho, B.; Masha, R.; Saziwa, T. (South African Journal of Higher Education, 2019)
This paper is based on a study that was conducted at a university based in the Eastern Cape, South Africa. The research aimed to explore and describe challenges that are likely to limit the success of postgraduate research students, mostly focusing on the relationship between students and supervisors. The study adopted a case study design with qualitative data. A self-constructed interview guide with open-ended questions was utilised as the main data collection tool from a sample of 34 postgraduate students from one faculty of the university in question. The study findings revealed that communication breakdown, poor feedback, non-availability of some supervisors and lack of ethical consideration were some of the major factors that contributed to negative supervisory experiences of the students who participated in the study. Based on the findings, the study recommended a number of intervention strategies that could be put in place for both students and supervisors to improve the supervision experience. Among these are the adoption of collaborative cohort model, supervisor training and communication guidelines.